Solve for b (2b-3.4)/0.6=-29

Math
2b-3.40.6=-29
Multiply both sides of the equation by 0.6.
2b-3.4=-29⋅0.6
Remove parentheses.
2b-3.4=-29⋅0.6
Multiply -29 by 0.6.
2b-3.4=-17.4
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Add 3.4 to both sides of the equation.
2b=-17.4+3.4
Add -17.4 and 3.4.
2b=-14
2b=-14
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2b=-14 by 2.
2b2=-142
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2b2=-142
Divide b by 1.
b=-142
b=-142
Divide -14 by 2.
b=-7
b=-7
Solve for b (2b-3.4)/0.6=-29

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top